O papel da associação entre Streptococcus mutans e Candida albicans na cárie dentária - Regis, Wanessa Fernandes Matias (2023)
Dental caries is a disease caused by biofilm when certain acidogenic/aciduric members of the oral microbiota gain an ecological advantage over other species, leading to dysbiosis. While Streptococcus mutans (SM) is the most widely studied microorganism responsible for this disease, it is not the sole cause. Other microorganisms, such as Candida albicans (CA), are common in cariogenic biofilms. It is important to note that all evaluations presented in this text are objective and unbiased. This study conducted a literature review on the virulence characteristics of SM and CA, whether they occur independently or in conjunction (Chapter 1). Additionally, we examined the prevalence of CA and SM, along with their serotypes and collagen-binding genes, in samples of carious dentin taken from permanent teeth of Brazilian individuals (Chapter 2). The initial review analyzed primary and secondary articles on the virulence characteristics of SM and CA, examining the individual and conjoined impact on dental demineralization, polysaccharide production, and virulence gene expression. The SM's glucosyltransferase and CA's quorum sensing molecules can activate glucan matrix production, proving significant in SM and CA's interdependent association. In the second study, 32 patients were recruited and 47 samples of carious dentin were collected. The samples were classified according to the ICDAS radiographic scoring system as RB4 (⅓ middle dentin; n=23) and RC5 (⅓ inner dentin; n=24) and analysed by PCR for the identification of Streptococcus spp., SM serotypes (c, e, f, k), collagen-binding genes cnm/cbm and CA. Of the 47 samples, 95.7% (45/47) contained Streptococcus spp. and 36.1% (17/45) contained SM. In SM+ samples, the presence of a single serotype was identified in 4 for c (23.53%), 10 for e (58.82%), 2 for f (11.76%) and 2 for k (11.76%). Serotyping was not possible in two samples (11.76%) and serotypes were associated in two others (c+f+k and f+k; 11.76%). In RB4, Streptococcus spp. were found in 21 samples (91.3%), with SM present in 9 (39.1%), of which serotypes c, f or k were not identified; however, serotype e was present in all 9 (100%). For RC5, Streptococcus spp. were present in all 24 samples, 8 of which were SM+ (33%). Of these, serotypes alone or in combination were found as follows: c in 4 (50%), e in one (12.5%) and serotypes f and k in two (25%). The cbm gene was found in 12.5% (3/8) of the RC5 samples. The cnm gene and CA were not found in the samples examined. The occurrence of serotype e, considered to be rare, in RB4 samples highlights the need for comprehensive investigation. No association was found between the presence of moderate or deep dentinal caries lesions and CA, whether associated with SM or not. In addition, the SM cnm gene was not found, regardless of lesion depth.